HUBUNGAN AKTIVITAS BEROLAHRAGA DENGAN TOLERANSI STRES PADA MAHASISWA LAKI-LAKI FAKULTAS KEDOKTERAN - Prida Harkina; Vira Sandayanti; Ahmad Yunus Feryaldi (Universitas Muhammadiyah Lampung, 2020)
Stres was a condition that was close to our daily life, including to male students of medical faculty. Curriculum methods, large and integrated study materials demand, also long-term study times, could be enough stresors. Exercising has many benefits, not only physically but also to practice our response to stres condition. This study aimed to find relationship between exercise activities with stres tolerance, with hypothesis there were relationship between exercise activities with stres tolerance on male medical faculty students. Subjects on this study were 88 male students from medical faculty of Malahayati University. This study was an observation analytic study with cross sectional approach. Result data analyzed used Mann Whitney Test, with p value <0,05. The result of bivariate test using Mann Whitney shown that there was relationship of exercise activity with stres tolerance with p = 0,000 (p > 0,05). Keywords:, Medical Faculty Students, Exercising Stres, Tolerance.